Administração crônica de melatonina sobre o tecido ósseo de ratas com hipoestrogenismo induzido - Castro, Milena Rossales (Universidade Federal de São Carlos, 2024)
Hypoestrogenism is associated with imbalances in bone tissue. Hormonal deficiency compromises bone remodeling and increases the chances of fractures. In this context, melatonin has been studied as a promising pharmacological method and an alternative to treatments with adverse effects. However, bone is not a simple organ to modulate, and there are inconclusive findings in the literature regarding the appropriate hormonal protocol to observe impacts on bone properties. In the present study, we evaluated the effects of chronic melatonin administration under hypoestrogenism conditions on bone parameters commonly compromised by estrogen deficiency. Forty female Wistar rats were randomly divided into four groups: control group (GC); ovariectomized group (GO); melatonin group (GM); and ovariectomized + melatonin group (GOM). GO and GOM underwent bilateral ovariectomy at 15 weeks of age to induce hypoestrogenism. One week later, daily administration of melatonin (10 mg/kg) by orogastric gavage began, during the animals' nighttime period, over 12 weeks. After this intervention period, femurs were collected and bone tissue analyses were conducted, including metric, physical, chemical, and mechanical measurements. Data are presented as mean ± standard deviation and were analyzed using two-way ANOVA to compare the effects of ovariectomy (OVX) and melatonin (MEL), with Newman-Keuls post-hoc test at a 5% significance level. The results show that MEL increased bone length (F=10.02, p<0.05), with no effect from OVX. OVX reduced bone density (F=28.76, p<0.01) and mineral density (F=50.34, p<0.01), with no effect from MEL. OVX increased bone water content (F=29.58, p<0.01) and reduced mineral percentage (F=36.87, p<0.01), with no effect from MEL on both. In the cortical fracture test, OVX had no effect on maximum load and fracture load, while MEL increased both properties (F=9.93, p<0.01; F=7.36, p<0.05). For calcium and phosphorus content, there was no significant effect from OVX and MEL. Overall, OVX caused impairments in bone parameters, and MEL had partial beneficial effects, but was not effective in neutralizing all the consequences of estrogen deficiency. Despite this, considering the comprehensive analysis of the investigated parameters, hormonal treatment showed potential in mitigating bone quality deterioration in contexts of osteometabolic disorders induced by hypoestrogenism.
Chronic administration of melatonin on bone tissue of rats with induced hypoestrogenism
Keywords: Ovariectomia; Densidade mineral óssea; N-acetil-5-metoxitriptamina; Osteopenia; CIENCIAS BIOLOGICAS::FISIOLOGIA